2020
DOI: 10.1017/s0033291720001130
|View full text |Cite
|
Sign up to set email alerts
|

Prospective predictors of decline v. stability in mild cognitive impairment with Lewy bodies or Alzheimer's disease

Abstract: Background Mild cognitive impairment (MCI) may gradually worsen to dementia, but often remains stable for extended periods of time. Little is known about the predictors of decline to help explain this variation. We aimed to explore whether this heterogeneous course of MCI may be predicted by the presence of Lewy body (LB) symptoms in a prospectively-recruited longitudinal cohort of MCI with Lewy bodies (MCI-LB) and Alzheimer's disease (MCI-AD). Methods A prospective cohort (n = 76) aged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
12
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 38 publications
3
12
3
Order By: Relevance
“…Alzheimer's disease (AD) and dementia with Lewy bodies (DLB) are the two most common neurodegenerative causes of dementia, between them accounting for 79% of cases in a UK brain bank study 1 . Both these diseases have a mild cognitive impairment (MCI) prodrome, and we have reported that MCI with Lewy bodies (MCI‐LB) has a faster decline and increased conversion to dementia compared with MCI‐AD, 2,3 which is consistent with evidence that at the dementia stage people with DLB have more rapid decline 4 and decreased survival times 5 compared with AD.…”
supporting
confidence: 86%
“…Alzheimer's disease (AD) and dementia with Lewy bodies (DLB) are the two most common neurodegenerative causes of dementia, between them accounting for 79% of cases in a UK brain bank study 1 . Both these diseases have a mild cognitive impairment (MCI) prodrome, and we have reported that MCI with Lewy bodies (MCI‐LB) has a faster decline and increased conversion to dementia compared with MCI‐AD, 2,3 which is consistent with evidence that at the dementia stage people with DLB have more rapid decline 4 and decreased survival times 5 compared with AD.…”
supporting
confidence: 86%
“… 21 In a subset of this cohort, we have also previously found that those with MCI-LB were more likely to feature a progressive decline in cognitive scores than patients with MCI-AD. 3 Our results here indicate that this also manifests in a greater annual risk of developing dementia than MCI-AD.…”
Section: Discussionsupporting
confidence: 49%
“…We previously identified that visual hallucinations were associated with a poorer cognitive prognosis in a subset of this cohort (n = 70), but this association was not observed with fluctuating cognition 3 ; the daily variation in cognitive function characteristic of this symptom may obscure progressive decline in cognitive measures but still manifest in more clinically relevant functional declines as seen here (i.e., someone may score better on the day of a research cognitive assessment but at home show increased reliance on caregivers as a direct consequence of the intermittent but significant “lows” associated with this clinical symptom).…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…While mild cognitive impairment is part of the normal cognitive changes that occur in dementia (Sanford, 2017), cognitive dysfunction is a symptomatic domain identified in many mental disorders such as major depressive disorder, which contributes significantly to occupational and functional disability (Pan et al., 2019). Furthermore, functional cognitive disorders are a group of overlapping conditions in which cognitive symptoms are present but are inconsistently experienced and unrelated to systemic or brain diseases (McWhirter et al., 2020); they are neurodegenerative in nature rather than subjective or functional (Hamilton et al., 2020). Approximately 25% of patients who visit memory clinics receive diagnoses that may indicate the presence of functional cognitive disorders (McWhirter et al., 2020), with a prevalence of 3%−19% among those older than 65 years old (Gauthier et al., 2006).…”
Section: Effects On Human Healthmentioning
confidence: 99%